GADD45B Transcript Is a Prognostic Marker in Papillary Thyroid Carcinoma Patients Treated With Total Thyroidectomy and Radioiodine Therapy - Barros-Filho, Mateus C.; de Mello, Julia B. H.; Marchi, Fabio A.; Pinto, Clóvis A. L.; da Silva, Igor C.; Damasceno, Patricia K. F.; Soares, Milena B. P.; Kowalski, Luiz P.; Rogatto, Silvia R. (Frontiers in Endocrinology, 2020)
Currently, the risk estimation of papillary thyroid carcinoma (PTC) recurrence is faulty. In this study, we enrolled 202 PTC patients submitted to total thyroidectomy and radioiodine therapy with long-term follow-up (median=10.7 years). The patients were classified as having favorable clinical outcome (PTC-FCO, no disease in the follow-up) or recurrence (PTC-RE). Alterations in BRAF, RAS, RET, and TERT were investigated (n=202) and the transcriptome of 48 PTC (>10 years of follow-up) samples was profiled. Although no mutation was associated with the recurrence risk, 68 genes were found as differentially expressed in PTC-RE compared to PTC-FCO. Pathway analysis highlighted a potential role of cancer-related pathways, including signal transduction and FoxO signaling. Among the eight selected genes evaluated by RT-qPCR, SLC2A4 and GADD45B showed down-expression exclusively in the PTC-FCO group compared to non-neoplastic tissues (NT). Increased expression of GADD45B was an independent marker of shorter disease-free survival [hazard ratio (HR) 2.9; 95% confidence interval (CI95) 1.2-7.0] in our cohort and with overall survival in the TCGA dataset (HR= 4.38, CI95 1.2-15.5). Although the assessed genomic alterations were not associated with the recurrence risk, GADD45B transcript was identified as a novel prognostic marker candidate in PTC patients treated with total thyroidectomy and radioiodine therapy.